O poder normativo dos sindicatos e a promoção da igualdade de oportunidades por meio de ações afirmativas - Ferreira, Dâmares (2011)
Studies and reports conducted by national and international organisms point out the existence of the negative discrimination, in Brazilian labor market. Admitting as base the brazilian constitutional law in vigour and the international conventions integrated to the national legal system, the present study searched if: the labor union has the obligation of studying and of proposing the creation of affirmatives actions, in the sense of increasing the equality to the access, to the training and to the promotion and maintenance of jobs, the equality of work conditions and of salaries among the workers and improvement of the fundamental right to reach equality of opportunities and non discrimination labor. In the development of the present study, the juridical nature of social base rights of workers, provided in 7° art. of Federal Constitution/88 was analyzed, as well as, the positive and negative linking of labor unions to the performance and implementation of themselves. Also, the juridical configuration of labor union liberty and of the normative power applied by the Federal Constitution of 1988 to them was showed. After these investigations, it was demonstrated that to the labor unions was imputed a syndical liberty contextualized and conditioned by other constitutional rules. And, in relation to the aspect of the authorization to create collective juridical orders, it was verified that the Federal Constitution of 1988 attributed to labor unions this power with the finality of, in the condition of legal agents of interests of this class members, can achieve a better social condition to worker, without losing sight of other constitutional landmarks. Especially in relation to the labor union, it was identified that, as a way of instrumentalize this search for improvement, it was attribute to the labor union the obligation of studying, of proposing and of negotiating the capable tools to its realization. Considering the discrimination scene that exists in brazilian labor market, the juridical nature of affirmative action was analyzed and it was infered that this instrument is constitutionally allowed and it is available to labor unions to, that during the exercise of normative power that they have, to stipulate conventional orders, wich increases the equality to the access, to the training, to the promotion and to the maintenance of jobs, the equality of work conditions and of salaries and improve the fundamental right to the equality of opportunities and non discrimination labor, provided for in items XXX e XXXI, of 7º art. of the Constitution